Automatic detection of voice disorders using self loop architecture in back propagation network - Murugesa Pandiyan, Paulraj, Prof. Madya Dr; Sazali, Yaacob, Prof. Dr.; Sivanandam, S. N.; Muthusamy, Hariharan, Dr. (Anna University, 2011)
Proceedings of International Conference on Signal Processing, Communications and Networking 2008 (ICSCN2008), organised by Department of Electronics Engineering Madras Institute of Technology, Anna University in association with AU-KBC Research Centre, 4th - 6th January 2008 at Anna University, Chennai, Tamilnadu, India.